Pengaruh Biaya Saluran Distribusi Terhadap Volume Penjualan - Dedeh Dedeh; Rita Meila Lestari (Akuisisi: Jurnal Akuntansi, 2018)
The free trade era now requires every company to work more effectively, efficiently and competitively. The strategies used by companies such as by improving the quality of product distribution channels, because the distribution channels of quality products can increase customer satisfaction so that sales volume can also increase. That way the company can grow more rapidly and the company's continuity can be maintained.The problem formulation of this research are: 1) How distribution channel cost in PD. Azkia Snack Ciamis? 2) What is the sales volume in PD. Azkia Snack Ciamis? 3) How much influence the distribution channel cost to sales volume in PD. Azkia Snack Ciamis?The purpose of this study to determine: 1) The cost of distribution channels in PD. Azkia Snack Ciamis. 2) Sales volume in PD. Azkia Snack Ciamis. 3) Influence of distribution channel cost to sales volume in PD. Azkia Snack Ciamis.The research method used is descriptive method, the writer will analyze descriptively about the influence of distribution channel cost to sales volume at PD Azkia Snack Ciamis. Data collection techniques in this study through observation, interviews and documentation.Based on the results of the research are known: 1) The cost of distribution channel in PD Azkia Snack Ciamis from 2012 - 2016 has increased, 2) Sales volume in PD Azkia Snack Ciamis from 2012 - 2016 has increased, but the percentage of change fluctuate, 3) which is positive with a very strong relationship between distribution channel cost to sales volume on PD Azkia Snack Ciamis, with coefficient value of corelai (rx1y) equal to 0,99, coefficient of determination value (KD) equal to 98,80%, and simple linear regression equation is Y = 112.83 + 7.03X with the number of tcount 15.74 and ttable 3.18. This shows that there is a positive relationship between distribution channel cost to sales volume so that Ha accepted and HO rejected. Keywords: Channel Cost Distribution, Sales Volume.